The The Development of Management Theories From an Academic Lens: A Systematic Literature Review and Current Challenges - Rachman, Faizal; Hendayana, Yayan (Garuda Prestasi Nusantara Consulting, 2025)
This article explores the evolution of management theories from an academic perspective by comparing the major theoretical schools from classical to contemporary thought. It aims to uncover the strengths, limitations, and research gaps within the management literature, while evaluating how these theories cope with globalization, digitalization, and economic change. The analysis is supported by historical trend data and visualizations. The findings suggest that while classical and behavioral theories retain partial applicability, contingency and dynamic capability theories offer more relevant frameworks for today's organizational challenges. Keywords: management theory; globalization; digitalization; leadership; dynamic capabilities